Gastrointestinal Tract Involvement of Gorham's Disease with Expression of D2-40 in Duodenum - Choi, Bong Seok (The Korean Society of Pediatric Gastroenterology, Hepatology and Nutrition, 2014)
We present a case of a 13-year-old boy with Gorham's disease involving the thoracic and lumbar spine, femur, and gastrointestinal (GI) tract, which was complicated by recurrent chylothorax and GI bleeding. The presenting symptoms were intermittent abdominal pain, back pain, and melena. Esophagogastroduodenoscopy and colonoscopy showed no abnormal lesions, but duodenal biopsy showed marked dilation of the lymphatics in the mucosa and submucosa, which revealed positive staining with a D2-40 immunohistochemical marker. In cases of GI bleeding with osteolysis, the expression of a D2-40 marker in the lymphatic endothelium of the GI tract may help to diagnose GI involvement in Gorham's disease. To the best of our knowledge, this is the first case report to pathologically demonstrate intestinal lymphatic malformation as a cause of GI bleeding in Gorham's disease.